Spin–orbit-coupling induced localization in the expansion of an interacting Bose–Einstein condensate - Chunlei Qu; Lev P Pitaevskii; Sandro Stringari (New Journal of Physics, 2017)
By developing a hydrodynamic formalism, we investigate the expansion dynamics of the single-minimum phase of a binary spin–orbit coupled Bose–Einstein condensate, after releasing from an external harmonic trap. We find that the expansion of the condensate along the direction of the spin–orbit coupling is dramatically slowed down near the transition between the single-minimum phase and the plane-wave phase. Such a slow expansion, resembling a form of an effective localization, is due to the quenching of the superfluid motion which results in a strong increase of the effective mass. In the single-minimum phase the anisotropic expansion of the Bose gas, which is spin balanced at equilibrium, is accompanied by the emergence of a local spin polarization. Our analytic scaling solutions emerging from hydrodynamic picture are compared with a full numerical simulation based on the coupled Gross–Pitaevskii equations.